2023
DOI: 10.1093/humupd/dmad009
|View full text |Cite
|
Sign up to set email alerts
|

Insights from Mendelian randomization and genetic correlation analyses into the relationship between endometriosis and its comorbidities

Abstract: BACKGROUND Endometriosis remains a poorly understood disease, despite its high prevalence and debilitating symptoms. The overlap in symptoms and the increased risk of multiple other traits in women with endometriosis is becoming increasingly apparent through epidemiological data. Genetic studies offer a method of investigating these comorbid relationships through the assessment of causal relationships with Mendelian randomization (MR), as well as identification of shared genetic variants and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(3 citation statements)
references
References 122 publications
0
2
0
Order By: Relevance
“…We report for the first time a genetic correlation between UFs and migraine. Recently, a significant genetic correlations was reported between endometriosis and migraine 37 . These findings linking genetically migraine to several women’s reproductive diseases stresses further the need to dig into these shared molecular mechanisms, especially that migraine is a neurovascular disorder predominantly affecting women.…”
Section: Discussionmentioning
confidence: 99%
“…We report for the first time a genetic correlation between UFs and migraine. Recently, a significant genetic correlations was reported between endometriosis and migraine 37 . These findings linking genetically migraine to several women’s reproductive diseases stresses further the need to dig into these shared molecular mechanisms, especially that migraine is a neurovascular disorder predominantly affecting women.…”
Section: Discussionmentioning
confidence: 99%
“…Two-sample bi-directional MR analysis explores both directions of causality, providing a comprehensive comprehension of the association between exposure and outcome variables. MR studies have been conducted to explore the causal relationship between depression and PCOS 21 , endometriosis 22 , and ovarian cancer 23 . However, to date, there is a lack of systematic MR studies that have revealed the causal association between depression/dysthymia and other female reproductive disorders.…”
Section: Introductionmentioning
confidence: 99%
“…The comorbidities with the highest frequency in our study cohort are listed. The "Other" comorbidities section includes inflammatory traits (celiac disease, Crohn's disease and multiple sclerosis), gastrointestinal features (chronic gastritis) and mental disorders (anxiety, ADHD, bipolar and personality disorders) based on McGrath et al's (2023) review[49].…”
mentioning
confidence: 99%